ECONOMIC PROBLEMS OR CRISIS OF ECONOMIC SCIENCE (Globalization and Business, 2023)
The collapse of the socialist system in the 90s of the last century and the break-up of the Soviet Union put the issue of transition from the administrative-com- mand economy to the market economy on the agenda. It was necessary to carry out a proper economic policy based on a certain theoretical basis, but the events have clearly demonstrated the limitations of the current level of economic science; it was impossible to predict the economic problems faced by these countries, while at the same time it did not have theoretical justification for their solution. The global financial crisis that began in 2008 has actually turned down the viewpoints of the visible representatives of economic science and greatly damaged the reputation of economic science.These circumstances have raised some questions about economic science and gave some researchers the grounds for assessing such a situation of economic sci- ence as a crisis situation.The situation of  economic science can be called crisis in that case when serious problems arising in real economy and the tasks facing the economy cannot be solved by the methods existing in the arsenal of economic science, or economic science has no answers to the ways and methods of solving these tasks. Consequently, economic science had been in crisis periods in 1929-1932, so called “Great Depression”, the collapse of the socialist system or the 2008-2009 financial crisis periods.Some researchers link the dangers of economic sci- ence to the diversity of economic theories and consider the latter to be one of the forms of crisis detection, which is not valid. The existence of different versions of economic theories is not due to the crisis situation of economic science, but because of the peculiarities of the emergence of each new economic theory. Unlike the exact and technical sciences, economic theory does not eliminate previous theories, but expands its borders on the development and diversification of economics. So the hard economic situation of a particular country is caused by other factors, not by the diversity of economic theories or the crisis situation of economic science.